Concentration levels and source apportionment of ultrafine particles in road microenvironments. (March 2016) - Argyropoulos, G.; Samara, C.; Voutsa, D.; Kouras, A.; Manoli, E.; Voliotis, A.; Tsakis, A.; Chasapidis, L.; Konstandopoulos, A.; Eleftheriadis, K.
Abstract: A mobile laboratory unit (MOBILAB) with on-board instrumentation (Scanning Mobility Particle Sizer, SMPS; Ambient NOx analyzer) was used to measure size-resolved particle number concentrations (PNCs) of quasi-ultrafine particles (UFPs, 9–372 nm), along with NOx, in road microenvironments. On-road measurements were carried out in and around a large Greek urban agglomeration, the Thessaloniki Metropolitan Area (TMA). Two 2-week measurement campaigns were conducted during the warm period of 2011 and the cold period of 2012. During each sampling campaign, MOBILAB was driven through a 5-day inner-city route and a second 5-day external route covering in total a wide range of districts (urban, urban background, industrial and residential), and road types (major and minor urban roads, freeways, arterial and interurban roads). All routes were conducted during working days, in morning and in afternoon hours under real-world traffic conditions. Spatial classification of MOBILAB measurements involved the assignment of measurement points to location bins defined by the aspect ratio of adjacent urban street canyons (USCs). Source apportionment was further carried out, by applying Positive Matrix Factorization (PMF) to particle size distribution data. Apportioned PMF factors were interpreted, by employing a two-step methodology, which involved (a) statistical association of PMF factor contributions with 12 h air-mass back-trajectories ending at the TMA during MOBILAB measurements, and (b) Multiple Linear Regression (MLR) using PMF factor contributions as the dependent variables, while relative humidity, solar radiation flux, and vehicle speed were used as the independent variables. The applied data analysis showed that low-speed cruise and high-load engine operation modes are the two dominant sources of UFPs in most of the road microenvironments in the TMA, with significant contributions from background photochemical processes during the warm period, explaining the reversed seasonal variation of UFP concentrations, compared to those observed in cities across Northern Europe. It was also demonstrated that town planning exerts a profound effect on the mitigation of traffic emissions. Highlights: Mobile measurements of UFPs were performed on various road microenvironments. PMF was applied to particle size distribution data for source apportionment. Two distinct vehicle exhaust emission patterns are the dominant sources of UFPs. Background photochemical processes also contribute significantly in the warm period.